GRB 140102A: insight into prompt spectral evolution and early optical afterglow emission. Issue 3 (1st June 2021) - Gupta, Rahul; Oates, S R; Pandey, S B; Castro-Tirado, A J; Joshi, Jagdish C; Hu, Y-D; Valeev, A F; Zhang, B B; Zhang, Z; Kumar, Amit; Aryan, A; Lien, A; et al.
ABSTRACT: We present and perform a detailed analysis of multiwavelength observations of GRB 140102A, an optical bright GRB with an observed reverse shock (RS) signature. Observations of this GRB were acquired with the BOOTES-4 robotic telescope, the Fermi, and the Swift missions. Time-resolved spectroscopy of the prompt emission shows that changes to the peak energy ( E p ) tracks intensity and the low-energy spectral index seems to follow the intensity for the first episode, whereas this tracking behaviour is less clear during the second episode. The fit to the afterglow light curves shows that the early optical afterglow can be described with RS emission and is consistent with the thin shell scenario of the constant ambient medium. The late time afterglow decay is also consistent with the prediction of the external forward shock model. We determine the properties of the shocks, Lorentz factor, magnetization parameters, and ambient density of GRB 140102A, and compare these parameters with another 12 GRBs, consistent with having RS produced by thin shells in an interstellar medium like medium. The value of the magnetization parameter ( R B ≈ 18) indicates a moderately magnetized baryonic dominant jet composition for GRB 140102A. We also report the host galaxy photometric observations of GRB 140102A obtained with 10.4 m GTC, 3.5 m Calar Alto Astronomical Observatory, and 3.6 m Devasthal optical telescope and find the host (photo z = 2.8^+0.7_-0.9 ) to be a high-mass, star-forming galaxy with a star formation rate of 20 ± 10 M_ yr^-1 .